2021
DOI: 10.1108/gkmc-07-2020-0097
|View full text |Cite
|
Sign up to set email alerts
|

Research evaluation of computer science publications using Altmetrics: a cohort study of Indian Central Universities

Abstract: Purpose Social interaction applications and reference tools are actively used by researchers to share and manage their research publications. Thus, this paper aims to determine the scholarly impact of selected Indian central universities. Design/methodology/approach This study analyzed 669 articles having both Dimensions citations and Altmetric attention scores published by 35 Indian central universities for 4 subfields of Computer Science using Altmetric Explorer. This paper determined each university’s con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
0
4
0
2
Order By: Relevance
“…En varios de los artículos seleccionados para esta revisión se reconoce a los artículos de revista como instrumento para la difusión de resultados en las diferentes disciplinas (Borku Uysal et al, 2021;Garcovich et al, 2020;Guallar et al, 2020;Lamba et al, 2020;Sun y Xia, 2016).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…En varios de los artículos seleccionados para esta revisión se reconoce a los artículos de revista como instrumento para la difusión de resultados en las diferentes disciplinas (Borku Uysal et al, 2021;Garcovich et al, 2020;Guallar et al, 2020;Lamba et al, 2020;Sun y Xia, 2016).…”
Section: Resultsunclassified
“…Como explica Lamba (2020), desde la democratización del acceso a internet a finales de la década de 1990 principios del siglo XXI, la forma en la que los investigadores intercambian y manejan la información ha cambiado mucho (Lamba et al, 2020), lo que ha facilitado que aumente la importancia de las métricas alternativas como una forma complementaria de medir el impacto. Gracias a la web social y a las nuevas métricas, los investigadores tienen hoy en día nuevas opciones para respaldar un artículo publicado a través de una web o en las redes sociales (Garcovich et al, 2020).…”
Section: Resultsunclassified
“…Social media indicators are widely used to evaluate academic achievements, and many of them have a positive correlation between citation and online attention scores (Thelwall and Nevill, 2018; Huang et al. , 2018; Lamba et al. , 2021; Nuzzolese et al.…”
Section: Resultsmentioning
confidence: 99%
“…Total cites has a moderate positive correlation with the indicators values of journal discourse leading (0.361 ≤ r ≤ 0.765), indicating a significant overall consistency. Social media indicators are widely used to evaluate academic achievements, and many of them have a positive correlation between citation and online attention scores (Thelwall and Nevill, 2018;Huang et al, 2018;Lamba et al, 2021;Nuzzolese et al, 2019;Salajegheh and Dayari, 2019;Syamili and Rekha, 2017;Yang and Qi, 2021). Boetto et al (2021) used a sample of 212 scientific papers on COVID-19 and found a moderate correlation among traditional citations, social media citations, news and blog citations.…”
Section: Evaluation Of Discourse Leading For Integrating Altmetrics I...mentioning
confidence: 99%
“…However, Luc et al suggest that more comprehensive social media strategies should be tested rigorously for further validation of their results. Finally, we are aware of a recent study by Lamba et al [23], investigating altmetric attention score and citation counts to examine the productivity of research groups working in certain sub-domains of computer science. Based on Spearman's rank correlation, Lamba et al observe a weak to moderate positive relationship between citations and altmetric attention scores.…”
Section: Related Workmentioning
confidence: 99%